Atributos químicos e matéria orgânica em complexos florestais periodicamente inundados na restinga da marambaia - RJ - Paula, Ranieri Ribeiro; Pereira, Marcos Gervasio; Machado, Deivid Lopes [UNESP] (Universidade Federal de Santa Maria (UFSM), Centro Pesquisas Florestais, 2013)
This study aimed to evaluate and characterize the chemical properties of soil organic matter under two periodically flooded forest formations on the island of Marambaia, Rio de Janeiro. These formations differ on the degree of soil water saturation, caused by the influence of water table, and in the (F1) formation presents the water table nearer the surface compared to the (F2) formation. Samples were collected in layers from 0.00 to 0.05, 0.05-0.10 and 0.10-0.20 m. The soil properties evaluated were: pH, H+ + Al+ 3, Ca+2, Mg+2, Na+, K+, P, N, total organic carbon (TOC) and base saturation (V%), humin carbon fraction (C-HUM), carbon of humic acid fraction (HAF-C) and fulvic acid fraction carbon (FAF-C). Statistically higher pH values were observed for F1. In F2 there are higher values of Mg+2, P, N and V% value. Correlation was found between the concentrations of Mg+2, N, humic acid and fulvic acid with water table in F1, and water table in F2 with Na+ and K+. Fraction C-HUM was more representative of the total organic carbon, followed by C-HAF and C-FAF. The TOC levels were higher in F1. The C /N ratio was lower in F2, with values ranging between 9 and 12, and F1 were found higher values of this relationship, ranging from 9 to 15. Among the pathways of formation of organic soils in both areas it appears that the major route for organic matter accumulation is the inheritance route.
Chemical attributes and organic matter in forest complex seasonally flooded in restinga of marambaia, Rio de Janeiro state
Keywords: natural fertility; total organic carbon; humic substances; hydric saturation